The contributors of adaptive performance at Hicom Automotive Manufacturers (Malaysia) Sdn. Bhd. / Nur Sharina Burhan - Burhan, Nur Sharina (Faculty of Business and Management, 2018)
The purpose of this research is to find out the contributors of adaptive performance at Hicom Automotive Manufacturers (Malaysia) Sdn. Bhd. There are two objectives had been set in this study. First, to examine the relationship between organizational learning and adaptive performance. Second, to examine the relationship between career development and adaptive performance. In order to complete this study, the data was obtained from primary data through the distribution of questionnaires. Pertaining to that, 201 employees in Hicom Automotive Manufacturers (Malaysia) Sdn. Bhd. were chosen as respondent for this study. All the responses were returned back to the researcher. Then, all the collected data were analyzed by using Statistical Package for Social Science (SPSS). From the correlation testing, the result shows two independent variables which are organizational learning and career development have a significant relationship with adaptive performance. Moreover, the result also revealed that there are two contributors that influence adaptive performance. Besides that, hypotheses testing dispalys that all factors are accepted. In conclusion, it shows that organizational learning and career development could improve adaptive performance of employees